2015
DOI: 10.1016/j.ssnmr.2014.10.007
|View full text |Cite
|
Sign up to set email alerts
|

An NMR crystallographic approach to monitoring cation substitution in the aluminophosphate STA-2

Abstract: The substitution of the divalent cations Mg 2+ and Zn 2+ into the aluminophosphate (AlPO) framework of STA-2 has been studied using an "NMR crystallographic" approach, combining multinuclear solid-state NMR spectroscopy, X-ray diffraction and firstprinciples calculations. Although the AlPO framework itself is inherently neutral, the positive charge of the organocation template in an as-made material is usually balanced either by the coordination to the framework of anions from the synthesis solution, such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…variation in skew reflecting the change in point symmetry at the P site. Seymour et al recently carried out a detailed experimental and computational study of the Mg and Zn substitution in STA-2and observed a similar trend in 31 P isotropic shift for both materials [81]. 1 H and27 Al NMR spectra showed that loss of bridging OHwas the charge-balancing mechanism, and Co 2+ linkage contributed around 2000 to 3000 ppm to the position of the peak maximum.…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…variation in skew reflecting the change in point symmetry at the P site. Seymour et al recently carried out a detailed experimental and computational study of the Mg and Zn substitution in STA-2and observed a similar trend in 31 P isotropic shift for both materials [81]. 1 H and27 Al NMR spectra showed that loss of bridging OHwas the charge-balancing mechanism, and Co 2+ linkage contributed around 2000 to 3000 ppm to the position of the peak maximum.…”
mentioning
confidence: 74%
“…It might not be possible to generate models that correspond exactly to the "real" structure, and simplified approaches, aimed at understanding the relative variations in the NMR parameters, rather than determining their exact magnitude, have to Sn/Ti disorder in pyrochlore ceramics and F substitution into hydrous minerals. [9,11,69,[80][81][82][83][84][85][86] A better approximation for an aperiodic structure (particularly for low level disorder) can be obtained by using a repeating crystal composed of "supercells", as shown in Figure 9c, where the supercell is chosen to be sufficiently large to minimise the effect of any structural change on the neighbouring cells. It should also be noted that using a supercell increases the number of atoms to be treated explicitly, thereby increasing the computational cost.…”
Section: Calculation Of Nmr Parametersmentioning
confidence: 99%
“…In a continuation of their earlier studies, recently reviewed by the principal authors, Dawson, et al performed a systematic DFT investigation of the solid‐state 31 P NMR isotropic chemical shifts of the local structure of aluminophosphates, capable of providing information on the number of crystallographic phosphorus sites, their relative populations, and the positions of any dopant atoms in the framework. Based on the recently demonstrated simple relationship between the local structure around phosphorus atom (first of all, the mean P─O bond length and P─O─Al bond angle) and calculated at the DFT level 31 P NMR isotropic chemical shift, δ iso , for a series of calcined aluminophosphates, the authors extended this approach to "as‐made" aluminophosphates, illustrated in Figure .…”
Section: Computation Of 31p Nmr Chemical Shifts: Accuracy Factors Andmentioning
confidence: 99%
“…In a continuation of their earlier studies, [99,100,101,102,103,104,105,106] recently reviewed by the principal authors, [107] Dawson, et al [108] performed a systematic DFT investigation of the solid-state 31 P NMR isotropic chemical shifts of the local structure of aluminophosphates, capable of providing information on the number of crystallographic phosphorus sites, their relative populations, and the positions of any dopant atoms in the framework. Based on the recently demonstrated simple relationship between the local structure around phosphorus atom (first of all, the mean P-O bond length and P-O-Al bond angle) and calculated at the DFT level 31 P NMR isotropic chemical shift, δ iso , for a series of calcined aluminophosphates, [103] the authors extended this approach to "as-made" aluminophosphates.…”
Section: Complexes and Clustersmentioning
confidence: 99%